2019
DOI: 10.1016/j.dib.2019.104103
|View full text |Cite
|
Sign up to set email alerts
|

Numerical results for the multiobjective trust region algorithm MHT

Abstract: In this data article, we report data and numerical results related to the research article entitled ”A trust region algorithm for heterogeneous multiobjective optimization” by Thomann and Eichfelder in SIAM Journal on Optimization. The method MHT which is presented there is designed for multiobjective heterogeneous optimization problems where one of the objective functions is an expensive black-box function, for example given by a time-consuming simulation. Here, we present the data of numerical tests with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The heuristic approaches from Section 3 have been implemented in Matlab R2017a and tested on 20 test problems from [19,Tab. 1], [20]: BK1, CL1, IM1, T1, LE1, Schaffer2, VU1, FF (n = 2, 3, 4, 5), Jin1 (n = 2, 3, 5), lovison1 (constrained and unconstrained), lovison4 (constrained and unconstrained) and T4 (n = 2, 3). For reasons of comparison, the test problems do not contain expensive black box functions, but are all given analytically.…”
Section: Results Of Numerical Testsmentioning
confidence: 99%
See 3 more Smart Citations
“…The heuristic approaches from Section 3 have been implemented in Matlab R2017a and tested on 20 test problems from [19,Tab. 1], [20]: BK1, CL1, IM1, T1, LE1, Schaffer2, VU1, FF (n = 2, 3, 4, 5), Jin1 (n = 2, 3, 5), lovison1 (constrained and unconstrained), lovison4 (constrained and unconstrained) and T4 (n = 2, 3). For reasons of comparison, the test problems do not contain expensive black box functions, but are all given analytically.…”
Section: Results Of Numerical Testsmentioning
confidence: 99%
“…We summarize the findings and present individual results exemplarily. For more details on numerical tests for the method MHT and the test instances, see [19,20].…”
Section: Results Of Numerical Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…An initial study [45], comparing MHT against a weighted sum-based approach and direct multisearch for multiobjective optimization, concluded that the proposed approach can yield good results.…”
mentioning
confidence: 99%